Patients over 65 years are assigned lower ECOG PS scores than younger patients, although objectively measured physical activity is no different - Broderick, Julie; Kennedy, Michael (My University, 2014)
Objectives The Eastern Cooperative Group Performance Status (ECOG PS) is a widely used standard functional classification in oncology practice, the verbal descriptors of which refer to physical activity (PA). Little is known about the cut-off points of this scale and measured PA levels. This research investigated the relationship between PS assigned, objectively measured PA, and patient age. Materials and Methods One hundred ambulatory patients with treatment-naive cancer wore an accelerometer (RT3) for a mean (SD) of 5.6 (1.1) days before initial oncology evaluation and ECOG PS assignment. Results Seventy five participants (75%) were < 65 years and 25 were ≥ 65 years. Eighty nine (89%) were assigned an ECOG PS of 0 or 1 and 11% a PS of 2 or 3. A weak but significant inverse association was found between objectively measured PA and PS (rho = − 0.26, p = 0.01). Seventy one participants (80%) with a PS of 0 or 1 spent more than 50% of waking hours resting. Participants assigned a PS of 2–3 spent significantly more time resting than those assigned a PS of 0 (p = 0.01). Age ≥ 65 years was significantly related to PS assigned (p = 0.04), although the older cohort were no less sedentary than younger patients. Conclusion PA levels were low, but PS scoring reflected relative PA levels and differentiated between patients of PS 0 and 2–3. Chronological age was not predictive of activity levels, but older patients were assigned lower PS scores. Incorporation of objective PA measures may merit further investigation especially in the geriatric oncology setting.
PUBLISHED
Keywords: Geriatric assessment; Accelerometer;; Physical activity; Performance status;; Eastern Co-operative Oncology Group; Cancer